First record and conservation status of Allobates algorei (Anura: Aromobatidae) in Colombia - Acevedo, Aldemar A.; Armesto, Orlando; Meza-Joya, Fabio Leonardo (Zootaxa, 2019)
The Neotropical genus Allobates Zimmerman & Zimmerman (1988) is a large monophyletic clade composed of 54 described species distributed between Central America and South America (Frost, 2019; Grant et al., 2017). Twelve species have been recorded in Colombia, mostly distributed in the eastern flank of the Eastern Cordillera and Amazonian Region, although some species reach the Magdalena Valley and the Central and Western Cordillera (Acosta-Galvis, 2017).